Efecto de tres tinturas sistémicas en diferentes tiempos de deshidratación para tinturación de rosas (Rosa sp.) variedad vendela. - Soria Reyes, Boris Estuardo (2013)
The present investigation was to evaluate the best dye systemic dehydration at different times in the process tinturación of roses (Rosa sp.) Vendela variety. The dyes used were: Blue N01 2002, Blue ra 101 and Sky blue 2388, and, the time of dehydration of the stems were 3 to 4 hours. The research work was performed Canton Latacunga Cotopaxi province, parish Aláquez in Floriculture Rosalquez S.A. The field work was performed under ambient temperature 130C, 80% of relative humidity, heliophany 1.650 hours of average yearly and 2.820 m.s.n.m. The experimental design was a D.C.A. (Complete Randomized Design) factorial arrangement of 3 x 2 and 4 replications, data collection was carried out for 15 days, which was performed statistical analysis using Statistical Analysis System (SAS). ANOVA procedure was used for analysis of variance and Tukey test (0,05). We also performed an economic analysis of each study treatment. From the results it is established that the best treatment is the T6 (Sky blue 2388 + 4 hours), because it reaches 80% of flower bud intense hue. Treatment with higher net income and lower production cost/dyed intense the button T6 (Sky blue 2388 + 4 hours), treatment with lower net income and higher production cost/dyed intense the button T1 (Blue N01 2002 + 3 hours).